Innovations into industrial technology programmes of Nigerian Universities for effective application of mobile communication technologies and quality assurance of graduates - Jimoh Bakare; Hyginus Osita Omeje; Samson Oluwatimilehin; Samson Ikenna Nwaodo; Obe Pauline Ijeoma; Olusesan Johnson Ogunmilade; Ojo Ajiboye Olaoye (Institute of Advanced Engineering and Science, 2020)
The study innovated the industrial technology programmes of Nigerian Universities for effective application of mobile communication technologies and quality assurance of graduates. Five research questions guided the study while three null hypotheses formulated were tested at .05 level of significance. The study made use of descriptive survey design and was carried out in Enugu State, Nigeria.nThe participants for the study were 120 comprising of 67 lecturers ofmelectrical/electronic technology and 53 technologists of industrial technical education. A 97-item questionnaire was used as instrument for data collection. One hundred and eighteen copies of the questionnaire were retrieved. The data collected were analyzed using mean, factor analysis, standard deviation and improvement need index (INI) to answer the four research questions while analysis of variance was employed to test the hypotheses at .05 level of significance. Results revealed that 33 innovations for inclusion into programme of electrical/electronic technology. Furthermore, the results of the study revealed that teachers need improvement in implementing the innovated contents of electrical/electronic technology aspect of industrial technical education programme. Hence, there is need to package the findings of the study into training programme and use it for building the capacity of teachers of electrical/electronic technology in Nigerian universities.